The growth rate determinants of the upper and lower middle income countries in the context of the international crisis: A multivariate analysis - Calero Castillo, Ciro (2014)
In this paper we analyze the factors that characterize the growth rates that reached the upper middle and lower middle income countries in 2009 by the statical technique multivariant the discriminant analysis, for which it was decided a priori to establish two groups based on positive and negative growth rates to apply this technique. Resulting the discriminant function, which show us the relevant factors for discrimination, these are: public spending, the rule of law, the fertility rate and the index of democracy.